A proposed torque calculation model for multi-plate clutch considering boundary lubrication conditions and heat transfer. (August 2020) - Liang, Xiutian; Chen, Liqing; Wang, Yuming; Wan, Ling
Abstract: This study proposes a torque calculation model that incorporates the boundary conditions of the lubricant flow field and variation of oil film temperature. The lubricating oil not only has the function of transferring torque, and the heat exchange between the lubricating oil and the friction plate will also cause the changes in lubrication characteristics. The torque transfer equation of a multi-plate clutch as related to viscosity was derived by combining the three-dimensional Navier-Stokes equation with the boundary conditions of the lubricant flow field. Considering the impact of the heat dissipation of the flow field into the torque transfer of the multi-plate clutch, the traditional torque transmission equation was modified with a piecewise affine (PWA) method. Taking the vehicle transfer case as an example, the equation for the variation in oil film radial temperature was obtained through the thermodynamic model of a flow field. By applying the parameters derived from the temperature equation to the PWA torque transfer model, the values under four working conditions were calculated. The results show that the relative errors between the corrected torque value and the test value under the four working conditions were less than 10%. The formation of the torque stability value provided by the PWA torque transfer model was at least about 0.1s earlier than that of the conventional model and much closer to the test result. Thus, the PWA torque calculation model performed well in the calculation of transmission torque. A novel torque calculation model for the multi-plate clutch is proposed. A heat transfer model of flow field for multi-plate clutch is established. Effects of the pressure on oil film temperature change are investigated. Comparative analysis of simulation and experiment shows that PWA has advantages.